Prospective Multicenter Study of Myocardial Recovery Using Left Ventricular Assist Devices (RESTAGE-HF [Remission from Stage D Heart Failure]): Medium-Term and Primary End Point Results. Issue 21 (24th November 2020) - Birks, Emma J.; Drakos, Stavros G.; Patel, Snehal R.; Lowes, Brian D.; Selzman, Craig H.; Starling, Randall C.; Trivedi, Jaimin; Slaughter, Mark S.; Alturi, Pavin; Goldstein, Daniel; Maybaum, Simon; Um, John Y.; et al.
Abstract : Background: Left ventricular assist device (LVAD) unloading and hemodynamic support in patients with advanced chronic heart failure can result in significant improvement in cardiac function allowing LVAD removal; however, the rate of this is generally considered to be low. This prospective multicenter nonrandomized study (RESTAGE-HF [Remission from Stage D Heart Failure]) investigated whether a protocol of optimized LVAD mechanical unloading, combined with standardized specific pharmacological therapy to induce reverse remodeling and regular testing of underlying myocardial function, could produce a higher incidence of LVAD explantation. Methods: Forty patients with chronic advanced heart failure from nonischemic cardiomyopathy receiving the Heartmate II LVAD were enrolled from 6 centers. LVAD speed was optimized with an aggressive pharmacological regimen, and regular echocardiograms were performed at reduced LVAD speed (6000 rpm, no net flow) to test underlying myocardial function. The primary end point was the proportion of patients with sufficient improvement of myocardial function to reach criteria for explantation within 18 months with sustained remission from heart failure (freedom from transplant/ventricular assist device/death) at 12 months. Results: Before LVAD, age was 35.1±10.8 years, 67.5% were men, heart failure mean duration was 20.8±20.6 months, 95% required inotropic and 20% temporary mechanical support, left ventricular ejection fraction was 14.5±5.3%, end-diastolic diameter was 7.33±0.89 cm, end-systolic diameter was 6.74±0.88 cm, pulmonary artery saturations were 46.7±9.2%, and pulmonary capillary wedge pressure was 26.2±7.6 mm Hg. Four enrolled patients did not undergo the protocol because of medical complications unrelated to the study procedures. Overall, 40% of all enrolled (16/40) patients achieved the primary end point, P <0.0001, with 50% (18/36) of patients receiving the protocol being explanted within 18 months (pre-explant left ventricular ejection fraction, 57±8%; end-diastolic diameter, 4.81±0.58 cm; end-systolic diameter, 3.53±0.51 cm; pulmonary capillary wedge pressure, 8.1±3.1 mm Hg; pulmonary artery saturations 63.6±6.8% at 6000 rpm). Overall, 19 patients were explanted (19/36, 52.3% of those receiving the protocol). The 15 ongoing explanted patients are now 2.26±0.97 years after explant. After explantation survival free from LVAD or transplantation was 90% at 1-year and 77% at 2 and 3 years. Conclusions: In this multicenter prospective study, this strategy of LVAD support combined with a standardized pharmacological and cardiac function monitoring protocol resulted in a high rate of LVAD explantation and was feasible and reproducible with explants occurring in all 6 participating sites. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01774656. Abstract : Supplemental Digital Content is available in the text.